Effects of macro elements on biomass and ginsenoside production in cell suspension culture of Ngoc Linh ginseng {Panax vietnamensis Ha et Grushv.) - Thanh, Nguyen Trung; Anh, Ha Tuan; Yoeup, Paek Kee (VNU Journal of Science: Natural Sciences and Technology; Vol 24 No 3, 2008)
Abstract